Case Report: A Novel ARMC5 Germline Mutation in a Patient with Primary Bilateral Macronodular Adrenal Hyperplasia and Hypogammaglobulinemia - Vena, Walter; Morelli, Valentina; Carrabba, Maria; Elli, Francesca; Fabio, Giovanna; Muller, Ilaria; Lucca, Camilla; Maffini, Maria Antonia; Lania, Andrea Gerardo; Mantovani, Giovanna; Arosio, Maura (Frontiers in Genetics, 2022)
Primary bilateral macronodular adrenal hyperplasia (PBMAH) represents an uncommon cause of endogenous hypercortisolism. Since the first description in 2003 in a French cohort, many papers have been published describing families as well as isolated individuals affected with this condition, who were found to harbor a genetic variants in the armadillo-repeat containing 5 (ARMC5) gene, a tumor-suppressor gene with a still unknown role in the disease pathogenesis. Studies in rat models suggested a possible link between ARMC5 damaging variants and the impairment of the cell-mediated immune response, leading to a higher susceptibility to bacterial and viral infections. To our knowledge, we describe the first case of a patient affected by PBMAH with hypogammaglobulinemia and monthly relapsing human herpes simplex viral infections. After the detection of subclinical Cushing’s syndrome, a unilateral laparoscopic adrenalectomy was performed. Subsequent genetic analysis of ARMC5 performed on genomic DNA extracted both from the adrenal tissue and lymphocytes revealed a novel somatic frameshift variant in exon 1 (c.231_265del:p.A77Afs*13) and a novel germline variant in exon 6 (c.2436del: p.C813Vfs*104). After adrenalectomy, we observed a significant improvement of clinical features concerning both hypercortisolism and relapsing viral infections, thus suggesting a possible adjuvant role of hypercortisolism on a genetic-based derangement of the immune system.